International Collaborative Learning Using Social Media to Learn about Social Work Ethics and Social Media. Issue 3 (2nd April 2016) - Knowles, Alan James; Cooner, Tarsem Singh
Abstract: The widespread adoption of social media (SM) has created new ethical challenges for social workers in understanding the use of SM and professional practice. This paper describes a project where social work students participated in international collaborative blended learning using closed Facebook groups to explore ethical issues related to professional practice and SM. The learning design incorporated the use of an innovative smart phone app, an online video case scenario, and asynchronous collaborative learning. The results of students' evaluations, lessons learned and recommendations about the learning design are included in the discussion.